Perancangan Ulang Terminal Guntur Melati Garut Dengan Pendekatan Lokalitas - Kusuma Dewi, Tiara; Salayanti, Santi; Murdowo, Djoko (Telkom University, 2024)
Terminal Guntur Melati Garut is a Type A Bus Terminal located in Garut Regency that serves inter-provincial transportation (AKAP) and intra-provincial transportation within the province (AKDP). As a Type A terminal, the facilities at Terminal Guntur Melati are divided into main facilities such as waiting rooms and administrative buildings, as well as supporting facilities like toilets, mosques, food courts, and health rooms. According to data from the Directorate General of Land Transportation, Balai Pengelola Transportasi Darat Class II West Java, the average monthly passenger volume reaches 216,327 people with 18,635 buses per month. During the 2023 Nataru holidays, there was a 65% increase in arrivals. To attract public interest in mass transportation, Terminal Guntur Melati Garut has implemented various innovations such as live music, martial arts activities for children, local Garut culinary bazaars, and education related to transportation and road safety. The Ministry of Transportation supports the terminal's development with a